Insulin Sensitivity and Pancreatic β-Cell Function in Ecuadorian Women With Turner Syndrome - Álvarez-Nava, Francisco; Bastidas, Daniela; Racines-Orbe, Marcia; Guarderas, Jéssica (Frontiers in Endocrinology, 2020)
Objective: To assess insulin sensitivity and pancreatic β-cell function in an adult population of Ecuadorian individuals with Turner syndrome (TS). Design and Methods: This was a cross-sectional correlational study conducted in TS subjects (>20 years old; n = 38). A standard 2-h oral glucose tolerance test was performed in both women with TS and the reference group. Glucose, lipids, insulin, and C-peptide concentrations were measured. Homeostasis Model Assessment (HOMA) of Insulin Resistance, Quantitative Insulin Sensitivity Check Index, McAuley, Matsuda, and Belfiore indices were calculated to evaluate the degree of insulin resistance (IR). The pancreatic β-cell function was assessed using HOMA-β, basal C-Peptide Index (CPI), and CPII at 120′. Results: A higher prevalence of impaired glucose tolerance was found in TS subjects compared with the reference group. Although significant differences were found for glucose concentrations at 60′ and 120′ (but not at 0′), only the baseline insulin concentrations differed significantly between the two groups. The values of the IR indices were statistically different between study and reference groups. A significant number of TS subjects diagnosed with IR were differently classified according to the index applied. The concentrations of C-peptide at 0′ and 120′ of TS subjects were similar to those of the control group. In contrast, the CPI and CPII values in the study group were significantly lower than those in the control group. Conclusion: It is impossible to select the best surrogate method for the assessment of IR in women with TS. The CPI and CPII values could be preferable to other indices to assess the pancreatic β-cell function in TS subjects. Our findings suggest that IR and pancreatic β-cell dysfunction could be independent events in women with TS, and both conditions seem to be caused by the disease per se. Our results imply that early screening and intervention for TS would be therapeutic for TS women.